Anesthetic Approach for a Patient with Jeune Syndrome - Mehmet I. Buget; Emine Ozkan; Ipek S. Edipoglu; Suleyman Kucukay (Case Reports in Anesthesiology)
Jeune syndrome (JS) is an autosomal recessive disease also known as asphyxiating thoracic dystrophy. A narrow bell-shaped thoracic wall and short extremities are the most typical features of the syndrome. Prognosis in JS depends on the severity of the pulmonary hypoplasia caused by the chest wall deformity. Most patient deaths are due to respiratory problems at early ages. Herein, we report a case of JS patient, who was scheduled for femoral extension under general anesthesia. The severity of respiratory problems in JS patients is thought to diminish with age. Our case supported this theory, and we managed the anesthetic process uneventfully.